“We are all exiles” : exile and place in the poetry of Ee Tiang Hong, Wong Phui Nam and Shirley Geok-lin Lim - Cheng, Boey Kim (2020)
Exile is a dominant theme and trope in the poetry of the pioneer generation of Anglophone Malaysian poets Ee Tiang Hong, Wong Phui Nam and Shirley Geok-lin Lim. This essay traces the roots of exile in these three poets, exploring how the sense of displacement from cultural and political Malay hegemony has shaped their exilic poetics. It tracks the trajectory of their career and work to examine how exile governs their readings of place and belonging, of heritage and home. The essay follows Ee’s and Lim’s emigrant routes and examines how physical separation from their homeland opens up liminal spaces that their poetry negotiates, and foregrounds issues of ethnicity, nationality and diaspora that their post-migration work engages with. For Wong, a stayer, exile becomes a poetic strategy for dealing with the adversities facing the Anglophone writer in Malaysia. It also enables him to deal with problematic issues of identity and belonging, and view them from the distant perspective of remote classical Chinese poets. For Ee, Wong and Lim, exile as theme and metaphor, and as a poetic strategy, becomes the inescapable lens through which they see Malaysia and their history and identity as Straits-born Chinese or Peranakans, descendants of inter-marriages between Chinese immigrants and Malay inhabitants.